Experimental Study of Heat Pipe Solar Collector for Energy Supply to Heat Pump - Wahyu, Dian (-)
Heat pipe solar collectors with heat absorber with a size of 1.13 m x 2 m x 0.12 m with 1.87 m2 aperture area has been created and tested to produce hot water which will be used for energy supply to heat pump. Heat pipes are made using water as the heat carrier medium and use stainless steel mesh wick 100 as a tool that helps accelerate the flow of condensate inside the heat pipe. Tests conducted heat pipe heat pipe first before selected and assembled into a solar water heating collectors. Testing is done by using heat pipes 1.000 mL 100 oC temperature hot water as a heat source and a heat pipe evaporator also tested by direct solar radiation. The tests are done to see the response speed (Ï) heat pipe in heat transfer. Filling ratio obtained from testing the best heat pipe is 10%. Testing of solar collector with heat pipe absorber has been conducted during the month of June 2013 in the laboratory of solar Institut Teknologi Bandung (ITB) using the standard American Society of Heating, Refrigerating and Air Conditioning Engineers (ASHRAE 93-2003). The efficiency of solar water heating collectors is strongly influenced by solar irradiance and the temperature difference between incoming fluid collector with the environment (Tfi-Ta). The test results showed the highest efficiency of 35.8% is obtained when the temperature difference between incoming fluid and ambient temperature is close to zero. To get hot water at a flow rate of at least 50oC 0,25 L / min, the necessary irradiance of 750 W / m2. Generally, during the trial obtained water output temperature solar heating collectors from 8:30 - 9: 40 pm and 15: 40 - 17: 30 pm is below 50 Â°C, while at 9:40 - 15: 40 obtained collector output water temperatures above 50 Â° C , Thus, it can be concluded that the heat pipe solar collectors are designed can be used to replace the evacuated tube collector in supplying heat for the heat pump. An advantage of using heat pipe solar collectors tend to be more economical and can be domestically produced.